Evaluation of an Audio-haptic Sensory Substitution Device for Enhancing Spatial Awareness for the Visually Impaired. Issue 9 (September 2018) - Hoffmann, Rebekka; Spagnol, Simone; Kristjánsson, Árni; Unnthorsson, Runar
Abstract : SIGNIFICANCE: Visually impaired participants were surprisingly fast in learning a new sensory substitution device, which allows them to detect obstacles within a 3.5-m radius and to find the optimal path in between. Within a few hours of training, participants successfully performed complex navigation as well as with the white cane. PURPOSE: Globally, millions of people live with vision impairment, yet effective assistive devices to increase their independence remain scarce. A promising method is the use of sensory substitution devices, which are human-machine interfaces transforming visual into auditory or tactile information. The Sound of Vision (SoV) system continuously encodes visual elements of the environment into audio-haptic signals. Here, we evaluated the SoV system in complex navigation tasks, to compare performance with the SoV system with the white cane, quantify training effects, and collect user feedback. METHODS: Six visually impaired participants received eight hours of training with the SoV system, completed a usability questionnaire, and repeatedly performed assessments, for which they navigated through standardized scenes. In each assessment, participants had to avoid collisions with obstacles, using the SoV system, the white cane, or both assistive devices. RESULTS: The results show rapid and substantial learning with the SoV system, with less collisions and higher obstacle awareness. After four hours of training, visually impaired people were able to successfully avoid collisions in a difficult navigation task as well as when using the cane, although they still needed more time. Overall, participants rated the SoV system's usability favorably. CONCLUSIONS: Contrary to the cane, the SoV system enables users to detect the best free space between objects within a 3.5-m (up to 10-m) radius and, importantly, elevated and dynamic obstacles. All in all, we consider that visually impaired people can learn to adapt to the haptic-auditory representation and achieve expertise in usage through well-defined training within acceptable time. Abstract : Supplemental digital content is available in the text.